International business blunders : lessons for future managers - Williams, Densil A. (Emerald Publishing Limited, 2019)
Difference in the levels of progress between developed and developing countries poses significant challenges for firms from the developing world to operate successfully in markets in the developed world. However, as globalization deepens, firms in the developing world, like their counterparts in the developed world, are forced to look for markets outside of their domestic environment. Increasingly, firms in developing countries will have no choice but to look for markets in large and wealthy developed countries in addition to other similar developing countries.International Business Blunders will provide direct evidence from CEOs and international business managers within firms that have moved from their domestic market in the developing world to do business in the developed world. The insights from these cases will serve as invaluable lessons for other firms that are seeking to enter these physically and psychically distant markets. By highlighting the blunders that are made by firms that have braved entering markets in developed countries, this book will provide pedagogical examples of how to minimize the blunders that future managers might make.The book will serve as a valuable tool for international business managers, students in MBA programmes, and also scholars who are researching and writing in the area of business and management.